The Character of the Volunteer in the Poet's Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is devoted to the analysis of the poems of Mirzohid Botirov, one of our promising artists who have a place in modern Uzbek literature, "Ko’nglim bilan kimning ishi bor?", "Yozug'im-Allahning eng yorug’ xati". Illumination of the image of the soul in the poet's poetry, the reflection of the image of Babur, who lived with longing for the Motherland throughout his life, in bright colors, the unique aspect of his work was examined by studying the skill of using beautiful expressions and allusions.      Mirzohid Botirov is one of the favorite creators of Uzbek poetry, creating poetry collections such as "Khayrat chohlari", "Derazangni och", "Hayot simfoniyasi", "Eng yorqin maktab" and conquering hearts with his unique poems. It is also significant that in the poems written by him, the symbol of the heart is interpreted in a special way, the heartaches and psyche of the hero trying to find his identity, leaving an impression as warm writings of a burning soul.